Addressing Public Accountability through Implementation of Balanced Scorecard: Study Case on Directorate of Government Debt Securities, Ministry of Finance - HERI PRAPTOMO (Badan Pendidikan dan Pelatihan Keuangan - Kementerian Keuangan Republik Indonesia, 2017)
Accountability is something that needs to be in place on every business activity particularly on public sector. Parties who are assigned with authority/power in a certain public organization should be accountable. They will be watched and controlled by other parties, such as supreme audit board, society, and non-government organization, who require explanation and justification of their conduct. One of means to answer the need of accountability in governmental activities is the performance management, that is broadly designed to guide the organization achieving its visions or objectives, fostering efficiency and effectiveness. Balanced scorecard is one example of performance management tools in contemporary era. Can it be said the implementation of balanced scorecard in the government agency is an attempt to deliver accountability? By analyzing and evaluating one practice of balanced scorecard in certain organization under Ministry of Finance of the Republic of Indonesia, this paper finds that the concept of balanced scorecard can be implemented as a tool to answer the needs of public accountability. Through every scorecard built in Directorate of Government Debt Securities, this paper discovers several ideas of public accountability such as financial, process, and hierarchical accountability, have been addressed by the implementation of balanced scorecard. However, such indicator of that unit’s balanced scorecard needs to be reformulated to answer other idea of public accountability.